Effectiveness of first-aid education in road traffic crashes on non-healthcare professionals' knowledge, attitude, and skills: a systematic review - Ufashingabire Minani, Christine; Kim, Lam Soh; Abdul Manaf, Rosliza; K. C. Mani, Kulanthayan; Ibrahim, Buhari; Mohamed Dirie, Ahmed; Kim, Geok Soh (Taylor and Francis, 2023)
This review aimed to evaluate and synthesize information on the effects of first-aid education in road traffic crashes on knowledge, attitudes, and skills among non-healthcare professionals. A qualitative study was designed according to the Prepared Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards to evaluate three outcomes, knowledge, skills, and attitude. The search strategy was performed in five databases (Science Direct, Scopus, CINAHL Plus, PubMed, and Google Scholar) to retrieve primary studies published between January 2011 and December 2021. In addition, the full texts of randomized controlled trials conducted on adults were included. Among the 2,399 articles retrieved from the databases, 2,388 were discarded, and only five studies met the inclusion criteria and were used in the final analysis and synthesis. Three of the five studies suggested that knowledge and skills are crucial in differentiating outcome factors between intervention and control groups regarding the effectiveness of first aid education. However, two studies on attitude and behaviour toward first-aid found no discernible change between the intervention and the control group. Therefore, our review revealed that only a well-structured first aid education is crucial to leverage the knowledge and skills of non-healthcare professionals before first aid provision, not attitude or behaviours.